Interdependence, Perception, and Investment Choices: An Experimental Approach to Decision Making in Innovation Ecosystems - Adner, Ron; Feiler, Daniel (Organization Science, 2019)
We explore how decision makers perceive and assess the level of risk in interdependent settings. In a series of five experiments, we examine how individuals set expectations for their own project investments when their success is contingent on the success of multiple, independent partners. We find that individuals are subjectively more confident and optimistic in an interdependent venture when its chances of success are presented as separate probabilities for each component and that this optimism is exacerbated by a greater number of critical partners, leading to (1) the inflation of project valuations, (2) the addition of excessive partners to a project, and (3) overinvestment of effort in the development of one’s own component within an interdependent venture. We examine these dynamics in settings of risky choice (with exogenously given probabilities) and in an economic coordination game (with the ambiguity of agency and strategic risk). We conduct our study with a wide range of participant samples ranging from undergraduates to senior executives. Collectively, our findings hold important implications for the ways in which individuals, organizations, and policymakers should approach and assess their innovation choices in ecosystem settings.